2003
DOI: 10.1038/ng1273
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of biliary system to pancreatic tissue in Hes1-deficient mice

Abstract: The biliary system, pancreas and liver all develop from the nearby foregut at almost the same time in mammals. The molecular mechanisms that determine the identity of each organ in this complex area are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 28 publications
2
184
2
Order By: Relevance
“…Indeed, it has even been shown that endocrine clusters, including b-cells, occur naturally in the extrahepatic bile ducts of adult mice (Dutton et al, 2007). The plasticity of the early foregut endoderm is further demonstrated in global Hes1-deficient mice, where significant amounts of ectopic pancreatic tissue containing islets and acini were closely associated with the common bile duct (Sumazaki et al, 2004;Fukuda et al, 2006).…”
Section: Exocrine Cell Development Ducts and Centroacinar Cellsmentioning
confidence: 99%
“…Indeed, it has even been shown that endocrine clusters, including b-cells, occur naturally in the extrahepatic bile ducts of adult mice (Dutton et al, 2007). The plasticity of the early foregut endoderm is further demonstrated in global Hes1-deficient mice, where significant amounts of ectopic pancreatic tissue containing islets and acini were closely associated with the common bile duct (Sumazaki et al, 2004;Fukuda et al, 2006).…”
Section: Exocrine Cell Development Ducts and Centroacinar Cellsmentioning
confidence: 99%
“…Hes1 maintains progenitors by inhibiting the expression of these bHLH activators. Genetic inactivation of Hes1 up-regulates the expression of these bHLH activators, resulting in, for example, severe pancreatic hypoplasia and the formation of an ectopic pancreas (Fukuda et al, 2006;Jensen et al, 2000;Sumazaki et al, 2004). Hes1 is also expressed in the intestinal crypt, where stem cells and proliferating progenitors are located, and represses the expression of bHLH-type activator genes, Math1 and Ngn3, whose translational products promote the differentiation of secretory cells.…”
Section: Roles Of Hes Factors In Various Tissuesmentioning
confidence: 99%
“…Hes1 operates as a general negative regulator of endodermal endocrine differentiation, and defects in Notch signaling lead to accelerated pancreatic endocrine differentiation. 3 Hes1 is expressed in the extrahepatic biliary epithelium throughout development. In Hes1 knock-out mice, biliary epithelium ectopically expresses the proendocrine gene Neurog3, differentiates into pancreatic endocrine and exocrine cells and forms acini and islet-like structures in the mutant bile ducts, followed by the conversion of much of the extrahepatic biliary primordium to ectopic pancreas.…”
Section: The Biliary Tract Has Bipotential Differentiationmentioning
confidence: 99%
“…[3][4][5] Expression of Hes1 is controlled by the evolutionarily conserved Notch pathway. Hes1 operates as a general negative regulator of endodermal endocrine differentiation, and defects in Notch signaling lead to accelerated pancreatic endocrine differentiation.…”
Section: The Biliary Tract Has Bipotential Differentiationmentioning
confidence: 99%
See 1 more Smart Citation